Midostaurin: a magic bullet that blocks mast cell expansion and activation. (30th August 2017) - Valent, P.; Akin, C.; Hartmann, K.; George, T. I.; Sotlar, K.; Peter, B.; Gleixner, K. V.; Blatt, K.; Sperr, W. R.; Manley, P. W.; Hermine, O.; Kluin-Nelemans, H. C.; et al.
Abstract: Clinically relevant features in patients with systemic mastocytosis (SM) include the cosmetic burden of lesional skin, mediator-related symptoms, and organ damage resulting from mast cell (MC) infiltration in advanced forms of SM. Regardless of the SM variant, expansion of neoplastic MC in the skin and other organs is triggered by mutant forms of KIT, the most prevalent being D816V. Activation of MC with subsequent release of chemical mediators is often caused by IgE-dependent mechanisms in these patients. Midostaurin, also known as PKC412, blocks the kinase activity of wild-type KIT and KIT D816V, counteracts KIT-dependent growth of neoplastic MC, and inhibits IgE-dependent mediator secretion. Based on this activity-profile, the drug has been used for treatment of patients with advanced SM. Indeed, encouraging results have been obtained with the drug in a recent multi-center phase II trial in patients with advanced SM, with an overall response rate of 60% and a substantial decrease in the burden of neoplastic MC in various organs. Moreover, midostaurin improved the overall survival and relapse-free survival in patients with advanced SM compared with historical controls. In addition, midostaurin was found to improve mediator-related symptoms and quality of life, suggesting that the drug may also be useful in patients with indolent SM suffering from mediator-related symptoms resistant to conventional therapies or those with MC activation syndromes. Ongoing and future studies will determine the actual value of midostaurin-induced MC depletion and MC deactivation in these additional indications.